Carbon footprint of the photovoltaic power supply chain in China. (1st October 2019) - Guo, Xiaopeng; Lin, Kai; Huang, Han; Li, Yang
Abstract: With the increasing consumption of fossil fuels, environmental problems are becoming increasingly serious. To solve these problems, we must vigorously develop clean energy. To this end, China has promulgated many policies to support the development of photovoltaic energy. To study the carbon footprint of the photovoltaic power supply chain and calculate the reduction of carbon emissions, this article establishes a carbon emission mathematical calculation model for photovoltaic power generation systems during the production, transportation and waste treatment processes. The carbon emission reduction model is established by calculating the power consumption of the photovoltaic power supply chain and power generation throughout the life cycle and by using the 1 kW photovoltaic power generation system as an example to analyse the data. The results show that from the perspective of the supply chain, it can effectively reduce carbon emissions from photovoltaic power supply chains by improving raw material development technology to provide high development efficiency, optimizing parts production processes, replacing transportation vehicles with electric vehicles gradually, increasing waste recycling efficiency, and improving waste disposal methods. In 2017, compared with thermal power generation in China, photovoltaic power generation systems were used in areas where the solar radiation is effective for 1000 h–3000 h, the CO2 emission reduction could be considered to be between 1.738 GT and 3.078 GT, which have shown good carbon emission reduction effect. Graphical abstract: Image 1084233 Highlights: Calculate carbon emissions from photovoltaic supply chain with life cycle method. Photovoltaic carbon recovery period is 2 years when average annual beam is 3000 h. In 2017, photovoltaic carbon emission reduction in China is 1.738 GT–3.079 GT. Increasing waste recovery can effectively reduce photovoltaic carbon emissions.